Role of intrauterine balloon tamponade in controlling massive primary post partum haemorrage (TAJ: Journal of Teachers Association, 2018)
Postpartum haemorrhage (PPH) Remains a significant complication of child birth worldwide. The most common cause of PPH is uterine atony. Recently, uterine tamponade using intrauterine condom appearsto be an effective tools in the management of uncontrolled primary PPH. Objectives of our studywas to see the effectiveness of large volume fluid filled condom catheter in the management of primary PPH. Methods: a condom was inserted in the uterus by means of a size 16 rubber catheter and inflated with 250 to 300ml normal saline until the bleeding was controlled. The condom was kept in situ for 24 to 48 hours. Results: Out of 53 cases, PPH was controlled in 52 cases. One patient died as the patient was eclamptic & develped disseminated intravascular coagulation (DIC). No patient required surgical intervention. Conclusion: fluid filled intrauterine condom is an effective method in the management of primary PPH when usual measures & drugs fail to control PPH.TAJ 2016; 29(1): 52-54